Free Will - Mentalizing: Some Reasons to Consider Them a Single Phenomenon. The "Indeterminist" Point of View - Madonna, Federica (Advances in Social Sciences Research Journal, 2023)
The following essay aims to provide some arguments in favor of equality of the phenomena of mentalizing and free will; in order to be able to highlight the overlap, therefore, the equality of the phenomena concerned, it is desirable, methodologically, that the three characteristics of mentalizing (the cognitive effort of the self to “understand” the other; the processing time of the message and the presence of the You) be displayed as intrinsic properties to the free will in order to conclude that the field of intersoggetivity is an extension of the investigation of the latter and not a phenomenon in its own right. It will be argued, in fact, that “reading of the mind” is the answer to the accusation made against indeterminists about the physical localisation of causality sui generis. The latter, unduly exploiting the characteristics of mentalizing, would find in the “mind/brain” of the agent its manifestation, masking, however, the fact that the ontological nature of the same mentalizing is that of free will.